2013
DOI: 10.7546/cr-2013-66-5-13101331-14
|View full text |Cite
|
Sign up to set email alerts
|

Palaeogene Planktonic Foraminifera of the Republic of Macedonia

Abstract: The present study deals with the taxonomy of the Palaeogene planktonic foraminifera of the Republic of Macedonia. Five species belonging to two genera, one family (GLOBIGERINIDAE Carpenter, Parker, and Jones, 1862), and one superfamily are described for the first time from this part of the Balkan Peninsula. The studied micropalaeontological material was obtained from eight outcrop sections belonging to five sedimentary basins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The first data for Late Eocene (Priabonian) age, based on gastropods, bivalves, corals and nummulitids from the Tikveš basin, gave Maksimovič et al (1954). Later Stojanova (Stojanova, 2008;Stojanova et al, 2011Stojanova et al, , 2013Stojanova, Petrov, 2012) also confirmed the Upper Eocene-Oligocene range of these sediments. The found association of benthic foraminifers and nannofossils in the upper flysch lithozone of Tikveš Paleogene basin gives an opportunity to identify a biostratigraphic subzone -Bolivinа which belongs to the zone Planulina costata (Bugrova, 1988) and nanofossil zone NP19 -NP 21 (section Krivolak).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The first data for Late Eocene (Priabonian) age, based on gastropods, bivalves, corals and nummulitids from the Tikveš basin, gave Maksimovič et al (1954). Later Stojanova (Stojanova, 2008;Stojanova et al, 2011Stojanova et al, , 2013Stojanova, Petrov, 2012) also confirmed the Upper Eocene-Oligocene range of these sediments. The found association of benthic foraminifers and nannofossils in the upper flysch lithozone of Tikveš Paleogene basin gives an opportunity to identify a biostratigraphic subzone -Bolivinа which belongs to the zone Planulina costata (Bugrova, 1988) and nanofossil zone NP19 -NP 21 (section Krivolak).…”
Section: Introductionmentioning
confidence: 78%
“…),Džuranov et al {1999);Stojanova (2008);Stojanova et al (2011Stojanova et al ( , 2013;Stojanova, Petrov, 2012, 2014;.SERTA SECTIONThe Serta section is located in the northeastern part of the Tikveš basin, 4 km SW of the village of Leskovica (Figure2), and it comprises about 100 m of the lower flysch unit. It is represented by conglomerates of 1.3 m thick and layers of clays and marls with a thin interlayers of sandstones by 0.15-2.5 m thick (within the lower part), and alternating layers of clays and sandstones (within the upper part).…”
mentioning
confidence: 99%
“…They are located in two tectonic zones -the Vardar Zone and the Serbo-Macedonian Massif [ 1 ]. The studied micropalaeontological material was obtained from the upper flysh unit [ 2 ] that is developed in 5 of totally 7 sedimentary basins [ 3 ]. The investigated agglutinated and porcelaneous specimens were established in 45 samples picked from 7 outcrop sections belonging to 4 of the basins (Fig.…”
mentioning
confidence: 99%